MICROGREENS SEBAGAI TREND HEALTY FOOD DI HOTEL DAN RESTORAN YOGYAKARTA - Irawati, Novi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2017)
Microgreens, the young seedlings of herbs, vegetables, beans, seeds, and grains, contain four to six times the vitamins and phytochemicals found in mature leaves of the same plants. The content of vitamins and other compounds in microgreens very beneficial for your health, because it can prevent the emergence of dangerous diseases, such as cancer. Microgreens cultivation technique is very easy and can be harvested from the age of 7-14 days. The manner of presentation is also very easy because it can be consumed without cooking first. To enjoy vegetable salad microgreens can be used as a breakfast menu or any other menu. It is very precise serve as one of the menu healthy food in hotels and restaurants, especially in Yogyakarta. Keywords: Mcrogreens, healthy food, hotel and resto